Numerical simulation on the effect of infiltration and evapotranspiration on the residual slope - Abdul Halim Hamdany (2023)
Soil suction plays an important role in governing the stability of slopes. Environmental sustainability could be jeopardized by hazards, such as slope failures (forest destruction, landscape alteration, etc.). However, the quantification of the suction effect on slope stability is a challenging task as the soil suction is usually affected by the precipitation and evapotranspiration. Numerical simulation plays an important role in the estimation of contour in soil suction due to rainfall and evapotranspiration as long-term and widespread monitoring is rarely conducted. The result of numerical simulation is highly dependent on the accuracy of the input parameters. Hence, suction monitoring plays an important role in verifying the result of numerical simulation. However, as a conventional tensiometer is limited to 100 kPa soil suction, it is hard to verify the performance of numerical simulation where suction is higher than 100 kPa. The osmotic tensiometer developed by Nanyang Technological University (NTU) can overcome this problem. It is now possible to monitor changes in soil suction higher than 100 kPa (up to 2500 kPa) for an extended period in the field. In this study, a procedure was proposed to estimate suction changes in residual soil based on rainfall and evapotranspiration data. Numerical simulation was carried out based on the soil properties and geometry of a residual soil slope from Jurong Formation Singapore. Changes in soil suction due to rainfall and evaporation were simulated and compared with the readings from the NTU osmotic tensiometers installed at 0.15 m and 0.50 m from the slope surface in the field. It was observed that numerical simulation was able to capture the variations of suctions accurately at greater depths. However, at shallow depths, erratic suction changes due to difficulties in capturing transpiration.